E-PRIME AS AN INSTRUCTIONAL TOOL IN TEACHING WRITING THE MULTILINGUAL STUDENTS - Khazhgaliyeva, G.Kh. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
Although this variant of English has not commandeduniversal acceptance, people from all walks of life have found that using E-Primeimproves their writing. The author tried out E-Prime in her writing classes and foundit a useful pedagogicand instructional tool. In conclusion she suggests that writing instructors of E-Prime assist to improve the multilingual students’ writing skills.
Keywords: instructional tool; multilingualism; writing skills; vocabulary; grammatical structure; writing assignments; descriptive devices; appropriate linguistic transformation